THE INDONESIA-MIDDLE EAST BUSINESS CYCLE SYNCHRONIZATION - Agustiar, Memet (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2023)
This study aims to analyze the business cycle synchronization (BCS) between Indonesia and 14 Middle Eastern countries and its determinants. The BCS was measured using BCS Index. The panel data was analysed using Feasible General Least Square with estimated coefficients. The results show that the Indonesia-Middle East BCS is strong in terms of index and trend. Trade openness positively and significantly affects the BCS. This study provides evidence for the endogeneity of trade relations and the BCS. Price factors, such as inflation and exchange rates, are more difficult to forecast. This information allows stakeholders to promote Indonesia"™s open trade policies and liberalization in the Middle East. This study proposes an update for how Indonesia and Middle East have benefited from the openness of trade and investment that exists between them. The BCS indices and trends in the two regions are important sources for expanding their economic partnership.JEL: E32, F13, N95, C33.